The Study of Type I Collagen by Immunoblotting in Samples of Bone-Plastic Biomaterials - Medvedeva, T.N.; Volova, L.T.; Kulagina, L.N. (Biomedical Chemistry: Research and Methods, 2023)
The type I collagen was studied in samples of two types of osteoplastic materials produced in the Biotech Research Institute of the Samara State Medical University using immunoblotting. The demineralized samples used in the work were compact bone powder and crushed material of human cancellous bone tissue. Collagen and its polypeptides were separated in a 5% polyacrylamide gel with 3.6 M urea according to the method of Hayashi and Nagai (1979). The advantage of the method is the separation under these conditions of type I and III collagen, as well as the α1(I) and α2(I) chains of type I collagen. Immunoblotting was carried out by diffusion method according to the method of Towbin et al. (1979) using nitrocellulose membranes (Santa Cruz, USA). Primary goat polyclonal antibodies to denatured collagen, 1:500 dilution (Millipore) were used. Peroxidase-conjugated secondary antibodies (mouse vs. goat), 1:80000 dilution (Sigma) were used also. It has been established that the bulk of the compact bone protein is localized between the α1- and α2-fractions of collagen. In samples of cancellous bone tissue, a molecular reduction of the protein is noted. Protein macromolecules with a gradually decreasing molecular weight and low molecular weight polypeptides migrating in the gel with a wide front up to the indicator line are detected. Due to the low specificity of osteoblast integrins in regenerating bone tissue, collagen polypeptides, as well as protein molecules retained in implants, can act as inducers of synthetic processes occurring in osteoblast nuclei. Protein fragmentation products in the implant can act as signaling molecules that trigger cascades of enzymatic reactions and intracellular signaling pathways.